Políticas monetária, cambial e bancária no Brasil sob a gestão do conselho da Sumoc, de 1945 a 1955 - Figueiredo Filho, João Sidney de (2005)
This essay is a study of the performance of the Currency and Credit Board Sumoc (deliberative tier) in the Brazilian monetary, exchange and banking policies from 1945 to 1955. The Sumoc was created to exert central bank functions in Brazil, as well as to pave the way for the eventual creation of the Brazil's central bank itself. For a better comprehension of the economic situation in which the Sumoc played its role, it was recovered from archives the undertaken attempts to create a monetary authority in Brazil. The study also shows the important role of the Sumoc in the Brazilian economic development, in the industrialization (including substitution of imported products) and in the implementation of the supporting politics for the national productive sector. Based on researches on primary sources - the records of meetings of the Sumoc and its issued instructions it was possible to bring back and analyze some relevant events and resolutions concerning monetary and exchange policies adopted by the Sumoc for instance the Instruction 70, which established multiple exchange tax, and the Instruction 113, which allowed foreign direct investments in capital goods and equipments, with no coverage of exchange. Besides that it was also analyzed the banking sector constitution, its crisis and how the Sumoc worked on these subjects. The annex includes a summary of Instructions issued by the Sumoc during the studied period.